2018
DOI: 10.3184/146867818x15319903829236
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Correlation Analysis of Reactivity in the Oxidation of Some α-Hydroxy Acids by Benzimidazolium Dichromate

Abstract: Kinetic and mechanistic studies of the oxidation of mandelic acid and nine monosubstituted mandelic acids by benzimidazolium dichromate (BIDC) in dimethyl sulfoxide are discussed with an emphasis on correlation of structure and reactivity. The reactions were of first order with respect to BIDC. However, Michaelis-Menten type kinetics were observed with respect to hydroxy acids. The reactions are catalysed by protons. The deuterium isotope effect for the oxidation of mandelic acid ( kH/ kD = 5.91 at 298 K) indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore, the transfer of hydride-ion from secondary alcohol to the BIFC is suggested. The bigger role of cation-solvating power of the solvents also supports the hydride ion transfer mechanism 41 . The hydride ion transfer can occur either via an acyclic bimolecular reaction or may occur due to the involvement of a cyclic, planner and symmetrical transition state of chromate ester.…”
Section: Mechanismmentioning
confidence: 64%
See 1 more Smart Citation
“…Therefore, the transfer of hydride-ion from secondary alcohol to the BIFC is suggested. The bigger role of cation-solvating power of the solvents also supports the hydride ion transfer mechanism 41 . The hydride ion transfer can occur either via an acyclic bimolecular reaction or may occur due to the involvement of a cyclic, planner and symmetrical transition state of chromate ester.…”
Section: Mechanismmentioning
confidence: 64%
“…The polar transition state is also supported by the observed negative value of entropy of activation 28 . The solvent effect has also indicated that the intermediate state is more polarized than the reactant [40][41][42][43][44][45][46][47][48] . Finally, we can say that BIFC is a very effective, mild oxidant, which can be used for the synthesis of ketonic compounds.…”
Section: Mechanismmentioning
confidence: 99%
“…For this study, many Cr(VI) derivatives have been reported [1][2][3][4][5] . The oxidation study of a-hydroxy acids by PBC 6 , PDC 7 , PCC 8 , IDC 9 , QCC 10 , PzCC 11 , MCC 12 , TEACC 13 , IFC 14 , PipCC 15 , MFC 16 , BIDC 17 etc. has been reported in DMSO.…”
Section: Introductionmentioning
confidence: 99%